A Polish Adaptation of the Oldenburg Burnout Inventory (OLBI) - Chirkowska-Smolak, Teresa (Studia Oeconomica Posnaniensia, 2018)
This paper concerns the psychometric evaluation of the Polish version of a self-report questionnaire to measure burnout - The Oldenburg Burnout Inventory. The aim of this study (N=945) is to validate the Polish version of the OLBI, and more specifically, to examine the factor structure, to evaluate its reliability (internal consistency), and its construct validity. In evaluating factorial validity I carried out an explanatory analysis, which revealed a 2-factor structure, although the construction of these factors differed from that in the original version. The other obtained results show, that despite this limitation, the Polish version of OLBI has good enough psychometric properties - the measure is reliable and its components correlates positively with perceived stress at work and negatively with job satisfaction. These finding suggest, that OLBI is an adequate measure of job burnout and it is recommended to use it in Poland.